Upaya Menanggulangi Over Kapasitas Pada Lembaga Pemasyarakatan di Indonesia - Wulan Dwi Yulianti (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2020)
The problem is that the relationship between punishment and correctional facilities must be returned to the concept of rationality of crime prevention mechanisms. The focus of efforts to control crime is not only on preventing and overcoming crime but also on penal system policies that are oriented towards a prison. The problems in this research are: 1). How can efforts be made to overcome overcapacity in correctional institutions in Indonesia? This research uses a normative juridical approach, by examining and interpreting theoretical matters concerning the theory of the penal system in an effort to overcome overcapacity in correctional institutions in Indonesia. The results show that the government needs to immediately implement a new criminal system theory as an effort to overcome the overcapacity of correctional institutions throughout Indonesia, namely by applying the theory of Social Integrity, Rehabilitation Sanctions for Narcotics users, Restorative Justice Efforts and most importantly the need for a new KUHP and KUHAP The criminal system that has been running does not run on a system of imprisonment and imprisonment for criminals by taking into account the values of justice for victims of crime.